FEATURES OF THE CURRENT STATE OF THE BANKING SECTOR OF THE RUSSIAN FEDERATION AND THE MAIN TRENDS OF ITS DEVELOPMENT - M. R. Efimova (Publishing House of the State University of Management, 2019)
Reduction of the number of credit organizations in the banking sector of the Russian Federation has been considered. The paper has been based on the data of Statistical Bulletin of the Bank of Russia for 2015-2017 years. Attention has been paid to some problems of creating banks resources potential especially because of declining external financing. The problems of small and medium-sized banks, including the availability of state budget funds have been designated. The main characteristics of the dynamics of lending to non-financial organizations and individuals have been considered. A discrepancy between the high financial results of the banking sector and a very modest contribution to the investment activities of non-financial organizations has been noted. Particular attention has been paid to the difference in interest rates on loans and deposits for different categories of borrowers and depositors.